Остатки морских черепах из олигоценовых отложений Апшерона и Северного Устюрта - Асланова, С.М.; Пронин, В.Г.; Чхиквадзе, В.М. (Вестник зоологии, 1979)
Fossil remains of sea turtles from Kainozoic deposits of the USSR and some adjacent countries are analyzed. Paleogenic turtles of Apsheron and North Ustyurt, Romania as well as, probably, of the Turgai depression (the Central Kazakhstan) belong to the extinct species Glarichelys gwinneri (Wegner, 1911) previously known only from the Rupelian of the Western Germany.